2022
DOI: 10.1039/d1ee02920g
|View full text |Cite
|
Sign up to set email alerts
|

Reline deep eutectic solvent as a green electrolyte for electrochemical energy storage applications

Abstract: Deep eutectic solvents (DES) are an environmentally benign promising emerging class of versatile solvent systems. This paper proposes, for the first time, a new approach to the DES application of...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
60
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 103 publications
(70 citation statements)
references
References 69 publications
4
60
0
Order By: Relevance
“…This project included the construction of a Li-ion battery system using an anode material consisting of reduced graphene oxide coated Fe 3 O 4 . When comparing the device to a system constructed entirely of pure Fe 3 O 4 or pure Fe 2 O 3 , it was revealed that the energy storage capacity and good durability of the device significantly increased [92][93][94][95][96][97][98][99][100].…”
Section: Catalysts For Carbon-free Energy Storage and Conversion Tech...mentioning
confidence: 99%
“…This project included the construction of a Li-ion battery system using an anode material consisting of reduced graphene oxide coated Fe 3 O 4 . When comparing the device to a system constructed entirely of pure Fe 3 O 4 or pure Fe 2 O 3 , it was revealed that the energy storage capacity and good durability of the device significantly increased [92][93][94][95][96][97][98][99][100].…”
Section: Catalysts For Carbon-free Energy Storage and Conversion Tech...mentioning
confidence: 99%
“…Deep eutectic solvent (DES), as an emerging solvent, has been identified as offering new possibilities to replace traditional solvents in the field of organic and material synthesis, 18,19 separation, 20 electrochemistry, 21 and so on. DES is made of hydrogen-bond acceptors (HBAs) and hydrogenbond donors (HBDs) in a proper ratio under certain conditions.…”
Section: Introductionmentioning
confidence: 99%
“…1 The solvents are usually obtained by mixing Lewis or Brønsted acids and bases and can contain a variety of anionic/cationic species. These green solvents are, therefore, being explored in multiple applications, 1,2,4 ranging from electrochemical applications 2,5 to biocatalysis, 6 and CO 2 capture. 7,8 The mixture of choline chloride and urea at the molar ratio of 1 : 2, known as reline, was the first DES reported 3 and is probably the most studied mixture among DESs.…”
Section: Introductionmentioning
confidence: 99%